Kajian Mekanisme Kesesuaian Kegiatan Pemanfaatan Ruang (KKPR) Kegiatan Berusaha - Eko Suryaningsih; Firda Diartika; Tri Yoso Astanto; Loetvy Wahyuningtiyas; Syavitri Sukma Utami Rambe (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
The implementation of Spatial Utilization Activity Conformity (Kesesuaian Kegiatan Pemanfaatan Ruang/KKPR) is a key component of Indonesia's risk-based business licensing reform through the Online Single Submission Risk-Based Approach (OSS-RBA). Although intended to improve licensing efficiency, KKPR implementation at the local government level continues to face institutional and governance challenges. This study analyzes the implementation of KKPR in West Sumbawa Regency, an area with an economy heavily dependent on the mining sector, and identifies factors influencing its effectiveness. A qualitative descriptive case study approach was employed. Data were collected through document analysis of relevant regulations, Gross Regional Domestic Product (GRDP) statistics, KKPR application records, and interviews with relevant stakeholders. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, while source and method triangulation ensured data credibility. The findings reveal that the mining sector's average contribution of 83.20% to the regional economy increases pressure on spatial utilization, positioning KKPR not only as an administrative licensing requirement but also as an instrument for sustainable spatial governance. The study identified two licensing mechanisms: 241 automatically processed KKPR Confirmations and 41 KKPR Approvals that continue to face institutional constraints. In addition, the absence of a formally established KKPR Technical Team and Standard Operating Procedures (SOPs) demonstrates a gap between national regulatory reforms and local institutional capacity. The study concludes that effective KKPR implementation depends not only on national policies and digital licensing systems but also on institutional capacity, inter-agency coordination, and the economic characteristics of extractive-resource-dependent regions.